My rotten life - Lubar, David (Lubar, David. Nathan Abercrombie, accidental zombie, 2009)
Tired of continually having his feelings hurt by popular students and bullies, fifth-grader Nathan agrees to try an experimental formula, Hurt-Be-Gone, and becomes a half-dead zombie, a condition which, he soon discovers, has some real advantages.